Experimental Investigation on Strength and Deformation Characteristics of Red Sandstone at Strain Rates of 10−2∼55 s−1. (13th August 2020) - Shi, Jie; Luo, Zongmu; Liu, Huachao; Wang, Dan; Shen, Haipeng; Li, Zeng
Abstract : The mechanical properties of rocks under low to intermediate strain rate are of great importance for seismic engineering, rock impact, and blasting excavation. To study the strength and deformation characteristics of sandstone subjected to low-medium speed impact loading, the complete stress-strain relationships of uniaxial compression at strain rates of 10 −2 ∼55 s −1 were obtained utilizing MTS and drop weight impact test devices. It is indicated that the dynamic compressive strength of sandstone in the range of intermediate strain rate increases approximately linearly with the strain rate under the quasi-static loading condition, while increasing nonlinearly under the dynamic loading condition. The deformation and fracture process of sandstone still consists of pore compaction stage, elastic deformation stage, instable microcrack propagation stage, and brittle fracture stage. The peak stress, critical strain, and residual strain increase with an increase in the strain rate, and the corresponding fracture mode changes from shear failure to split failure. The evolution law of total absorbed strain energy with deformation coincides with that of stored elastic strain energy for sandstone at the intermediate strain rate. The effect of the strain rate on elastic strain energy is more significant than that of dissipated strain energy. Furthermore, both the brittleness and fracture degree of sandstone become more remarkable with the strain rate increasing.